E-089 Outcomes of mechanical thrombectomy in patients with neurological disorders. (4th August 2020) - Brasiliense, L; Abdulrazek, H; Aguilar-Salinas, P; Abbad, H; Dumont, T; El-Ghanem, M
Abstract : Introduction: As the number of patients undergoing mechanical thrombectomy (MT) increases in the United States, operators may be confronted with patients harboring preexistent debilitating neurological disorders. Still, the epidemiology and reperfusion strategies of patients with acute ischemic stroke (AIS) and neurological disorders has not been established. Methods: The National Inpatient Sample (NIS) Database was queried for the most recent 5-year period available (2012–2016). We identified patients with a diagnosis of ischemic stroke and the following neurological disorders: Alzheimer's Disease (AD), Parkinson Disease (PD), Amyotrophic Lateral Sclerosis (ALS), Multiple Sclerosis (MS), and Myasthenia Gravis (MG). Variables analyzed included mechanical thrombectomy, discharge home, length of hospital stay (LOS), and inpatient mortality. Results: A total of 460, 070 patients with ischemic stroke were identified. The prevalence of AD in this population was 2.3% (10, 775/460, 070), PD was 1.2% (5, 630/460, 070), MS was 0.31% (1, 430/460, 070), ALS was 0.012% (56/460, 070), and MG was 0.001% (9/460, 070). Mechanical thrombectomy was performed in 1.63% of the patients (7, 529/460, 070). Patients with co-existing neurological disorders underwent MT less often (0.65%; 118/17, 900) compared to other patients (1.67%; 7, 411/442, 170). Patients with AD were significantly less likely to be discharged home after MT compared to patients without co-existing neurological disorders (9% vs. 26%; p=0.0034), while patients with PD were less likely to be discharged home in the group without thrombectomy (32% vs. 51%; p<0.0001). Length of hospital stay was similar between groups (range 4.3 – 8.7 days). Inpatient mortality was significantly higher in patients with AD (5% vs. 4%; p<0.0001) and PD (5% vs. 4%; p=0.044) in the group that did not undergo MT. Conclusions: Patients with co-existing neurological disorders underwent mechanical thrombectomy at a lower rate compared to other patients. Further studies should elucidate factors affecting the rate MT in the United States. Disclosures: L. Brasiliense: None. H. Abdulrazek: None. P. Aguilar-Salinas: None. H. Abbad: None. T. Dumont: None. M. El-Ghanem: None.